Hard goals [ the secret to getting from where you are to where you want to be - Murphy, Mark A. [ (Mark Andrew)] (McGraw-Hill, 2011)
For managers who want to inspire a team or themselves to do extraordinary things, the ultimate guide to setting extraordinary goals that let them be up to 75% more successful